Polymorphisms rs562556 and rs2479409 of the PCSK9 gene associated with obesity and cardiovascular disease - Vašková, Hedviga; Poráčová, Janka; Šlebodová, Miriama; Kalafutová, Soňa; Konečná, Mária; Sedlák, Vincent; Kimáková, Tatiana; Mydlárová Blaščáková, Marta (Central European journal of public health, 2023)
OBJECTIVE: The primary objective was to comprehensively assess the association between single nucleotide polymorphisms (rs562556 and rs2479409) in the PCSK9 gene with biochemical parameters - C-reactive protein (CRP), glucose (GLU), triglyceride (TAG), low-density lipoprotein cholesterol (LDL CHOL), non-high-density lipoprotein cholesterol (non HDL CHOL), high-density lipoprotein cholesterol (HDL CHOL), cholesterol (CHOL), and anthropometric parameters (visceral fat), overweight/obesity and cardiovascular risk. METHODS: A total of 71 women aged 23-64 years were divided into three groups based on body mass index (BMI). BMI ≥ 25/≥ 30 kg/m2 was the criterion for assessment of overweight/obesity. Anthropometric, biochemical and genetic examinations were performed on the probands. Changes in markers in each group and their association with cardiovascular risk were monitored. RESULTS: We can conclude that in our study population we observed differences between the BMI categories for biochemical markers (CRP, LDL CHOL, non HDL CHOL, HDL CHOL, LDL CHOL) and anthropometric marker (visceral fat). Atherogenic index of plasma (AIP), Castelli's Risk Index I (CRI-I) and atherogenic coefficient (AC) confirmed high cardiovascular risk for the obese women category (0.045); (< 0.013); (< 0.010). Genotype and allele frequencies for the PCSK9 gene in the overweight and obese groups showed higher allele frequencies of allele A for both polymorphisms of the gene. CONCLUSIONS: PCSK9 gene expression is associated with biological processes such as lipid metabolism and inflammation. Cholesterol-lowering therapies are the gold standard for reducing the risk of cardiovascular mortality and morbidity. Administration of monoclonal antibodies (mAbs) against PCSK9 is a novel lipid-lowering therapeutic approach in adults to reduce the risk of cardiovascular disease.
Keywords: Proprotein Convertase 9; BMI; Obesity; Middle Aged; obesity; Adult; mladý dospělý; Overweight; Cholesterol; proproteinkonvertasa subtilisin/kexin typu 9; Cardiovascular Diseases; PCSK9; Young Adult; ženské pohlaví; Humans; women; lidé středního věku; obezita; nadváha; dospělí; Female; cardiometabolic risk; kardiovaskulární nemoci; lidé; cholesterol